Efektivitas Pendidikan Kesehatan Metode Peer Group Terhadap Pengetahuan, Sikap, Dan Perilaku Personal Hygiene Saat Menstruasi Pada Siswi Kelas 10 Di SMA Perguruan Rakyat 2 - Desvi Syam Wilis; Wintarsih Wintarsih (Universitas Malahayati Lampung, 2024)
ABSTRACT Health education is an effective approach in increasing understanding, attitudes, and actions regarding personal hygiene, especially during menstruation. The 2017 Indonesian Demographic Health Survey (IDHS), as many as 63.9% of young women still have bad hygiene practices during menstruation, and this is due to limited information and understanding regarding personal hygiene during menstruation. Writing intends to understand the effectiveness of peer group health education techniques related to understanding, attitudes, and personal hygiene actions during menstruation in 10th grade female students in SMA Perguruan Rakyat 2. This research used a quasy experimental one group pretest-posttest design. The population in this research was all 10th grade female students at the College of People's High School 2. The number of respondents was 55 students, before and after being given Health Education, the peer group was 55 people. The output results describe the paired sample correlation test or the relationship between the two data (pretest variables and posttest variables). According to the output, it is known that the significance value (Sig.) is 0.623. Because the value of Sig. 0.623 0.05, it can be concluded that there is no significant relationship between the pretest variables and the posttest variables. In conclusion, it was found that there were changes in knowledge, attitudes, and personal hygiene measures when menstruating in high school female students, where the results of the Paired sample T-test showed a sig score of 0.046, which means 0.000 0.05. Keywords: Peer Group Method, Personal Hygiene, Menstruation ABSTRAK Pendidikan kesehatan ialah satu diantara pendekatan yang efektif dalam meningkatkan pemahaman, sikap, serta tindakan tentang kebersihan pribadi, khususnya ketika menstruasi. Survei Demografi Kesehatan Indonesia (SDKI) 2017, sebanyak 63,9% remaja putri masih mempunyai tindakan kebersihan yang buruk ketika menstruasi, dan perihal tersebut dikarenakan oleh terbatasnya berita serta pemahaman terkait kebersihan diri sepanjang menstruasi. Penulisan bermaksud memahami efektifitas Pendidikan Kesehatan teknik peer group terkait pemahaman, sikap, serta tindakan personal hygiene ketika menstruasi pada murid perempuan kelas 10 di SMA Perguruan Rakyat 2. Riset ini memakai desain quasy eksperiment one group pretest-posttest design. Populasi pada riset ini semua murid perempuan kelas 10 di SMA Perguruan Rakyat 2. Jumlah responden 55 orang siswi, sebelum dan seusai diberikan Pendidikan Kesehatan peer group 55 orang. Hasil output tersebut memaparkan uji korelasi sampel berpasangan atau kaitan antara dua data (variabel pretest dan variabel posttest). Menurut output tersebut, diketahui bahwa nilai signifikansi (Sig.) adalah 0.623. Sebab nilai Sig. 0.623 0.05, bisa ditarik kesimpulan bahwasannya tidak ada kaitan yang signifikan antara variabel pretest dengan variabel posttest. Simpulan didapatkan bahwa ada perubahan pengetahuan, sikap, serta tindakan personal hygiene ketika menstruasi pada murid perempuan SMA, dimana hasil uji Paired sample T-test, ditunjukkan yakni skor sig 0.046, yang berarti 0,000 0.05. Kata Kunci: Metode Peer Group, Personal Hygiene, Menstruasi